Memoirs of the Court of St. Cloud (Being secret letters from a gentleman at Paris to a nobleman in London) $1 (BVolume 3s - Goldsmith, Lewis, 1763?-1846 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of the Court of St. Cloud" by Lewis Goldsmith is a historical account written in the early 19th century. The text consists of secret letters from a gentleman in Paris to a nobleman in London, providing insight into the political climate and intrigues surrounding Napoleon Bonaparte's court during the early 1800s. The letters detail the actions and characters of various prominent figures, including Kings and Ministers, set against the backdrop of the tumultuous period following the French Revolution. The opening of the book introduces us to the political landscape of Paris in August 1805, where the author describes the resilience and diplomatic strategies of the King and Queen of Naples amidst revolutionary challenges. It reflects on the notable figures at court, such as Chevalier Acton, who serves the King of Naples with loyalty and capability, maintaining influence despite external pressures from France. The narrative also touches on the intricate dynamics between various European powers and Napoleon's strategic machinations, as exemplified by the nuanced observations of the Ambassadors and government officials navigating their alliances and rivalries amidst the backdrop of a rapidly changing political atmosphere. (This is an automatically generated summary.)
Release date is 2004-12-04
Produced by David Widger
Keywords: Napoleon I, Emperor of the French, 1769-1821; France -- Court and courtiers; France -- History -- Consulate and First Empire, 1799-1815; France -- Kings and rulers -- Biography